An All-Conjugated, PM6-Based Block Copolymer Enables Stable Nanoparticle Dispersions in Methanol - Daum, Manuel; Aydan Alkan, Ecem; Gubanov, Kirill; Rocha-Ortiz, Juan S.; Maraslioglu, Cem; Cirpan, Ali; Fink, Rainer; Hauch, Jens; Heumüller, Thomas; Brabec, Christoph (Macromolecules, 2025)
Organic semiconductors are commonly processed using toxic halogenated or aromatic solvents due to their poor solubility in less harmful alternatives, leading to significant environmental and health concerns. Although there are “green” solvents available, these materials often face limited processing options and challenges in microstructure control. To mitigate this, an emerging approach involves creating dispersions of organic semiconductor nanoparticles in polar, environmentally friendly solvents. However, achieving stable nanoparticle dispersions without ligands remains a significant challenge. This study introduces a novel method for enhancing the stability of these ligand-free dispersions by developing an amphiphilic conjugated polymer, PM6-FNT, designed to form stable nanoparticles in alcohol-based dispersions. PM6-FNT is synthesized via a one-pot, stepwise Stille cross-coupling polymerization, where an amino group-functionalized fluorene-thiophene copolymer (FNT) chain is grown in situ on preformed PM6 chains. Nanoparticles of PM6-FNT, prepared by nanoprecipitation in polar solvents like alcohols, exhibited exceptional colloidal stability due to the high zeta potential of around 35 mV and controllable particle sizes in the range of 35–200 nm. In contrast, nanoparticle dispersions of PM6 could not be formed under the same conditions. This research highlights the potential of PM6-FNT to address existing challenges in organic semiconductor processing. Using nanoparticles instead of solutions enables enhanced layer-by-layer processing capabilities, morphology control, and higher crystallinity, further optimizing performance and paving the way for the eco-friendly, large-scale production of organic semiconductor devices.
CRIS-Team Scopus Importer:2025-12-05